The contribution of IITA improved cassava to food security in subSaharan Africa: an impact study - Bokanga, M.; Makinde, K.; Dixon, A.; Whyte, J.; Manyong, Victor M. (2000)
Since its foundation in 1967, the International Institute of Tropical Agriculture (IITA) has worked, in partnership with national agricultural research systems in sub-Saharan Africa, on the improvement of cassava and dissemination of improved cassava germplasm. This paper describes the impact of this work, by looking at the spread of improved cassava varieties, their use in national breeding programs, and the ultimate benefits of this work on food security in sub-Saharan Africa. Twenty countries were surveyed, which together account for over 90% of cassava production in sub-Saharan Africa. A total of 206 cassava varieties were released between 1970 and 1998 by the national agricultural research systems of these countries. Genetic materials from IITA represented the major source of germplasm used in the development of released varieties. In 1998, improved cassava varieties were grown on about 22% of the 9 million hectares that were planted to cassava in the 20 countries. The use of improved varieties resulted in a yield increase of 49% over the average yield, and an additional production of 10 million tonnes of fresh storage roots per year, or 2200 kcal per person per day for 14 million people. Between 1970 and 1998 a total of 1381 scientists were trained at IITA, accounting for 38% of senior and 49% of intermediate level researchers currently working in cassava research in these countries.